Development of Tourism in Surkhet: Prospects and Challenges - Dhakal, Aishwarya Prasad; Devkota, Bipana (International Journal of Atharva, 2025)
The main thrust of this paper is to discuss on the prospects and challenges for tourism development in Surkhet district, emphasizing the need for infrastructure improvement, capacity building, and people participation to create sustainable and inclusive tourism industry that benefits both government and local community. Surkhet district is culturally rich, linguistically homogeneous, and ecologically diverse area with massive potential for tourism development. Its rugged terrain, picturesque landscapes, and unique cultural heritage, offers opportunities for eco-tourism, sports tourism, cultural tourism, adventure tourism and community-based tourism. Despite its natural and cultural assets, tourism in the district has remained developing in the face of incomplete infrastructure and promotional efforts. This paper follows the qualitative method of research in descriptive and interpretative research design using field observation and focus group discussion (FGD). However, recent initiatives by both the government and local communities aim to enhance the development of tourism sector, focusing on preservation of local traditions, culture, and natural resources projected towards sustainable tourism development, employment generation and empowerment of community homestay.